Elizabeth Gaskell’s Smaller Stories - Lambert, Carolyn. author. aut Link
VIII, 201 p.
Keywords: “This is an engaging and insightful study. Highly polished and well argued, it affords a deeply researched and welcome perspective on Gaskell's short stories as an oblique and creative critique of 19th century society – and of Gaskell as literary stylist.” —Felicity James, Associate Professor in Eighteenth and Nineteenth Century Literature, University of Leicester “For its illuminating close readings of Gaskell's lesser-known short pieces, for its reappraisal of Gaskell as a more passionate and angrier writer than has previously be acknowledged, and for its knowledgeable exposition of her creative and professional processes, not to mention her personal and religious motivations, this is an important contribution to Gaskell studies that will also be of interest to scholars of Victorian publishing, popular fiction, and women's writing.” —Helena Ifill, Lecturer in English Studies, School of Language, Literature, Music and Visual Culture, University of Aberdeen This book re-locates Elizabeth Gaskell’s ‘smaller stories’ in the literary and cultural context of the nineteenth century. While Gaskell is recognised as one of the major novelists of her time, the short stories that make up a large proportion of her published work have not yet received the critical attention they deserve. This study re-claims them as an indispensable part of her literary output that enables us to better contextualize and assess her achievement holistically as a highly-skilled woman of letters. The periodicals in which Gaskell’s shorter pieces were published offer a microcosm of nineteenth-century society, and Gaskell took full advantage of the medium to apply a consistent and barbed challenge to cultural and gendered constructs of roles and social behaviour. Although her eminently readable prose still flows easily in her short stories, it is less likely to elide the sharp corners of domestic violence, the disabling experiences of women, the pain of death and loss, and the complications of family life. Carolyn Lambert is the author of The Meanings of Home in Elizabeth Gaskell’s Fiction (2013), co-editor with Marion Shaw of For Better, For Worse: Marriage in Victorian Novels by Women (2018) and the author of Frances Trollope (2020).